Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.4161/cc.5.4.2442
|View full text |Cite
|
Sign up to set email alerts
|

TFII-I: Connecting Mitogenic Signals to Cell Cycle Regulation

Abstract: Reproduction, or the faithful passage of genetic information from one cell to its progeny, is central to life. To achieve reproduction faithfully cells have developed the cell cycle during which error-free replication of DNA, followed by division of the nucleus and partitioning of the cytoplasm yields two daughter cells. Prior to committing to reproduction, cells must sense mitogen levels in their environment and transduce those signals to the nucleus through a series of biochemical steps, resulting in spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
(52 reference statements)
4
16
0
1
Order By: Relevance
“…Opn, important cytokine regulator, and Nedd8, involved in ubiquitination, were also identified as BEN-specific targets. TFII-I proteins are known to be involved in cell cycle regulation through their interaction with Rb protein (19) or regulation of cyclin D1 (20). Here, we have demonstrated that both BEN and TFII-I recruited to the promoter of Ccnd3, which supports the role of TFII-I transcription factors in the cell cycle.…”
Section: Rattus Norvegicussupporting
confidence: 54%
“…Opn, important cytokine regulator, and Nedd8, involved in ubiquitination, were also identified as BEN-specific targets. TFII-I proteins are known to be involved in cell cycle regulation through their interaction with Rb protein (19) or regulation of cyclin D1 (20). Here, we have demonstrated that both BEN and TFII-I recruited to the promoter of Ccnd3, which supports the role of TFII-I transcription factors in the cell cycle.…”
Section: Rattus Norvegicussupporting
confidence: 54%
“…Consistent with the fact that TFII-I delivers the growth factor dependent transcriptional signal to the cyclin D1 promoter, mutation of tyrosine residues in TFII-I, which are required for its mitogen mediated transcriptional activity, abolishes cyclin D1 gene expression (61). Thus, TFII-I may provide a molecular link between mitogen-dependent signaling and nuclear gene expression to control cell division and proliferation (62).…”
Section: Role Of Tfii-i In Cell Cyclementioning
confidence: 66%
“…Although ectopic expression of TFII-I results in elevated cyclin D1 levels and bypass radiation induced cell cycle block, it is undetermined whether these cells progress through cycle despite DNA damage or whether they undergo DNA repair (61,62). Moreover, it also remains to be shown whether TFII-I undergoes preferential degradation during particular phases of the cell cycle and what molecular mechanism(s) might govern this timed destruction (62).…”
Section: Role Of Tfii-i In Cell Cyclementioning
confidence: 99%
See 2 more Smart Citations